2009
DOI: 10.2208/kaigan.65.1271
|View full text |Cite
|
Sign up to set email alerts
|

Projection of Global Winds and Waves under Global Warming Scenario

Abstract: This study predicts future ocean wave climate in comparison with present wave climate based on the high resolution atmospheric general circulation model and global wave model. The annual average and extreme of sea surface winds and waves are analyzed in detail. There are clear regional dependence of annual average and extreme values from present to future climate. The wind speeds and wave heights of future climate are increased in middle latitudes and the Antarctic Ocean, and these are decreased in the equator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The observations of wave in Japan suggested that the annual maximum significant wave height tended to increase since 1991 (Sugawa et al, 2011). Mori et al (2009) showed that mean wave height around Japan at the end of 21 st century will be lower than that from 1979 to 2003, and that maximum wave height will be much higher. However, the future wave projection is still uncertain because the change of wave height depends on the climate condition.…”
Section: Introductionmentioning
confidence: 99%
“…The observations of wave in Japan suggested that the annual maximum significant wave height tended to increase since 1991 (Sugawa et al, 2011). Mori et al (2009) showed that mean wave height around Japan at the end of 21 st century will be lower than that from 1979 to 2003, and that maximum wave height will be much higher. However, the future wave projection is still uncertain because the change of wave height depends on the climate condition.…”
Section: Introductionmentioning
confidence: 99%
“…Mori et al (2009) shows that mean wave height around Japan will decrease at the end of 21st century, compared with it from 1979 to 2003, and that maximum wave height will be much higher clearly.…”
Section: Introductionmentioning
confidence: 97%
“…Regarding to recent studies, Mori et al (2009) indicated that the averaged wave conditions were evaluated quantitatively and had big differences in areas. Mori et al (2010) computed future surface winds and waves using the atmospheric general circulation model and global wave model.…”
Section: Introductionmentioning
confidence: 99%